An alternative method for measuring air-handling unit static pressure following ASHRAE Standard 37: Scenario 1—horizontal ducts with elbows (RP-1581). (18th May 2016) - Wheeler, Grant; Pate, Michael
Abstract : ASHRAE Standard 37 (ASHRAE 2005) describes the air-side testing setup for the indoor side (i.e., air-handling unit) of a residential air-conditioning or heat pump system for energy performance testing. Furthermore, ASHRAE Standard 37 requires a straight downstream duct that forms a vertical test section of a specified length based on the air-handling unit outlet geometry for measuring the outlet static pressure. A potential problem is that adding this duct to the unit may result in an overall test apparatus height that exceeds psychrometric test room dimensions. One possible solution investigated in this project is to create a horizontal test section by the addition of an elbow placed after the unit. The air-handling unit outlet static pressure can then be measured in this horizontal test section, which has the same length requirements as that specified by ASHRAE Standard 37 for the vertical section. This horizontal duct orientation with an elbow is referred to as Scenario 1, while a second approach based on installing a passive resistive device at the air-handling unit outlet is referred to as Scenario 2, which is the subject of a second article. Experimental tests were performed on 2-, 3-, and 5-ton units, with a variety of elbow types and orientations located at the unit exit. Experiments were also performed on the same three units with vertical test sections as described in ASHRAE Standard 37 (i.e., baseline data). Comparisons of these test results showed that ASHRAE Standard 37 can be modified to reduce testing height restrictions by using a horizontal test section providing a right-angled elbow with double-thickness turning vanes and installed at the air-handling unit outlet in a specific orientation relative to the rotating blower. Specifically, this research found that the test section height downstream of the air-handling unit outlet could be reduced by 51% to 64% for the three different units, namely 2, 3, and 5 tons. Furthermore, with regard to the height of either the vertical baseline or horizontal Scenario 1 test assembly located in a psychrometric test room, this study showed that air-handling unit tests could be successfully performed in a 9-ft-high (2.7-m) room that would otherwise require a 12-ft-high (3.7-m) room following ASHRAE Standard 37 requirements.